The Impact Of Phtps On Trip Quality, Trip Value, Satisfaction And Word Of Mouth Non-muslim Tourists Perspective - Mohamed Battour ,; Muhammad Khalilur Rahman ,; Md. Sohel Rana (Emerald Publishing Limited, 2024)
Indexed by SCOPUS/ERA